A New Perspective on Quality Evaluation for Control Systems with Stochastic Timing - Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter; Klaus, Tobias (Proceedings of the 21st International Conference on Hybrid Systems: Computation and Control (HSCC '18), 2018)
As control applications are particularly sensitive to timing variations, the Quality of Control (QoC) is degraded by varying execution conditions of the underlying real-time system. In particular, transitions between different execution or environmental conditions pose a significant issue as they may impact the QoC unexpectedly. So far, the QoC is usually evaluated either in a stationary, time-invariant way, which cannot analyse said transitions, or by simulation, which becomes inefficient when confronted with random influencing factors. In this paper, we propose a new perspective on QoC evaluation for modern, adaptive real-time systems with varying timing conditions. For this, we present a time-variant stochastic assessment approach that incorporates the effects mentioned before. Our results demonstrate that adaptive scheduling and runtime behavior considerably impacts the QoC. At the same time, the proposed scheme significantly outperforms a traditional simulatio
Keywords: Quality of Control; Jitter; Real-time Systems; Automatic Control; Embedded systems; cyber-physical systems; Real-time systems; real-time; scheduling

Antriebskoordinator am Beispiel eines Parallelhybridfahrzeugs - Michalka, Andreas; et al. (Methoden und Anwendungen der Regelungstechnik, Erlangen-Münchener Workshops 2007 und 2008, 2009)

Closing the loop: Towards control-aware design of adaptive real-time systems - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (2016 IEEE Real-Time Systems Symposium, RTSS 2016, 2016)

Control approaches for operating point stabilization of microring resonator modulators under fast perturbations - Cherian, Athira Jess; Michalka, Andreas; Murray, Kyle; Roell, Georg; Graichen, Knut (Proceedings Silicon Photonics XIX, 2024)

Control unit for a dry double clutch transmission - Genzel, Michael; Orend, Ralf; Michalka, Andreas; Pohlmann, Roger; et al. (6th Int. Symposium "Innovative Automotive Transmissions", 2007)

Ein modellbasiertes Gesamtkonzept zur Längsdynamiksteuerung und -regelung von Parallelhybridfahrzeugen - Michalka, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Die steigende Komplexität moderner Fahrzeugantriebe erfordert im Bereich der Steuerung und Regelung des Bewegungsverhaltens umfassende Betrachtungen auf Komponentenebene, aber vor allem auch auf Gesamtsystemebene. Gegenstand dieser Arbeit ist daher der gesamthafte Entwurf der Längsdynamik eines Fahrzeugs, das mit einem parallelen Hybridantriebsstrang ausgestattet ist. Dazu wird ein hierarchisches Strukturkonzept vorgestellt, das es ermöglicht, die Kernaufgaben der Schnittstellenbereitstellung zwischen Fahrer und Fahrzeug, der Sicherstellung eines energieeffizienten Betriebes sowie der definierten Einstellung des dynamischen Längsverhaltens des Fahrzeugs weitgehend getrennt voneinander zu betrachten und zu bearbeiten. Im Bereich der Längsdynamikauslegung kommt dabei ein neuer Ansatz zur Automatisierung des Antriebsstrangs zum Einsatz, der insbesondere Lastwechsel an Reibkupplungen - wie sie im betrachteten Doppelkupplungsgetriebe verwendet werden - leicht beherrschen lässt. Insgesamt ergibt sich damit ein Konzept, das dem Fahrer ein von ihm vorgegebenes Summendrehmoment auf Radebene für die Erfüllung seiner Fahraufgaben zur Verfügung stellt. Die Dynamik des Drehmomentaufbaus bleibt dabei unverändert, während gleichzeitig eine Aufteilung der Stellgrößen auf die redundanten Aktoren beispielsweise unter Effizienzgesichtspunkten erfolgen kan

Fault detection in gauge-sensorized strain wave gears - Kißkalt, Julian; Michalka, Andreas; Strohmeyer, Christoph; Horn, Maik; Graichen, Knut (European Control Conference, 2024)

Gesamtkonzept zur Steuerung und Regelung von Fahrzeugen mit Doppelkupplungsgetriebe - Michalka, Andreas; Orend, Ralf; et al. (VDI-Berichte Nr. 2029, 2008)

Kompensation von Drehmomentfehlern automatisierter Reibkupplungen durch beobachterbasierte Störgrößenaufschaltung - Michalka, Andreas; Roppenecker, Günter (VDI-Berichte Nr. 2233, 2015)

Kupplungsschlupfregelung als Teil eines Gesamtkonzepts zur Antriebsstrangsteuerung eines Parallelhybridfahrzeugs - Michalka, Andreas; Roppenecker, Günter; et al. (VDI-Berichte Nr. 2196, 2013)

Model-based fault simulation and detection for gauge-sensorized strain wave gears - Kißkalt, Julian; Michalka, Andreas; Strohmeyer, Christoph; Horn, Maik; Graichen, Knut (IFAC-PapersOnLine, 2025)

Modellbasierte Steuerungsberechnung für Doppelkupplungsgetriebe als Teil eines neuen Gesamtkonzepts zur Getriebesteuerung und -regelung - Michalka, Andreas; Roppenecker, Günter; Wurmthaler, Christoph; Orend, Ralf (VDI-Berichte Nr. 2009, 2008)

Modellbasierte Steuerungsberechnung für Doppelkupplungsgetriebe als Teil eines neuen Gesamtkonzepts zur Getriebesteuerung und - regelung - Michalka, Andreas; Roppenecker, Günter; Wurmthaler, Christoph; Orend, Ralf (At-Automatisierungstechnik, 2009)
This paper presents a model based concept for controlling powertrains with dual clutch transmission in passenger cars. It focuses a feedforward control approach for shift actions by applying a simple vehicle model. Both types of possible shift actions are considered: those with start and target gear on different input shafts (direct shift) as well as those with start and target gear on the same input shaft (indirect shift). © Oldenbourg Wissenschaftsverla
Keywords: Dual clutch transmission; Feedforward and feedback control of powertrain; Model based approach; Powertrain management

Poster Abstract: "Closing the Loop: Towards Control-aware Design of Adaptive Real-Time Systems" - Klaus, Tobias; Franzmann, Florian Peter; Gaukler, Maximilian; Michalka, Andreas; Ulbrich, Peter (Proceedings of the 37th Real-Time Systems Symposium (RTSS '16), 2016)

Rack force estimation from standstill to high speeds by hybrid model design and blending - Snobar, Fadi; Michalka, Andreas; Horn, Maik; Strohmeyer, Christoph; Graichen, Knut (IEEE International Conference on Mechatronics (ICM 2023), 2023)

Sensitivity-based moving horizon estimation of road friction - Snobar, Fadi; Michalka, Andreas; Horn, Maik; Strohmeyer, Christoph; Graichen, Knut (European Control Conference, 2024)

Simulation chain for sensorized strain wave gears - Kißkalt, Julian; Michalka, Andreas; Strohmeyer, Christoph; Horn, Maik; Graichen, Knut (Proc. 27th International Conference on System Theory, Control and Computing (ICSTCC), 2023)